Study of Community Participation in the Process of Villages Infrastructure Development on Program PNPM Mandiri in Jayapura Regency - Flora Yvonne de Quelyoe; Elsyan Reinette Marlissa; Sarlota Ratang (Journal of Social and Development Sciences, 2016)
Community participation in each process of public policy making is an important issue as the mirror of principle of democracy in a country. It would be very precise when participation of community later became one of the principles that should be implemented by the government in an effort to realize good governance. The importance of participation and form of participation given a supporting factor for the success of the government program. The aim of Road Infrastructure development program is to increase local community welfare so they are able to access a wide range economy, social and politic activities. For example, in economic activity, the local producer can easily carry and sell their product to the local market when compared to the previous moment when road was damaged, especially during the rainy seasons. Therefore it is necessary participation of community to engage in solving the road infrastructure problem in their respective villages and districts. This research is located in Jayapura Regency, and using explanatory research with qualitative approach. The Techniques of data collection on this study is using questionnaire, distributed to 80 respondents. The result of this research shows that community participation community in the planning, implementation and evaluation is very good. Community participation on implementation phase of National Program of Community Empowerment (PNPM Mandiri) is really determined by the level community involvement in the planning stages. The important reasons related to community participation are: a) the engagement of community, either directly or indirectly, are able to create feel of belongings to all public asset that has been built with high cost. b) Through community participation, they know about the limitation of government resources (funds, manpower). c) Involvement of local society in those development stages could be a control tools to supervise all development financing in the level of village, district, and regency as well.